2009
DOI: 10.1007/s11248-009-9252-5
|View full text |Cite
|
Sign up to set email alerts
|

Production of taxa-4(5),11(12)-diene by transgenic Physcomitrella patens

Abstract: Taxadiene synthase gene from Taxus brevifolia was constitutively expressed in the moss Physcomitrella patens using a ubiquitin promoter to produce taxa-4(5),11(12)-diene, the precursor of the anticancer drug paclitaxel. In stable moss transformants, taxa-4(5),11(12)-diene was produced up to 0.05% fresh weight of tissue, without significantly affecting the amounts of the endogenous diterpenoids (ent-kaurene and 16-hydroxykaurane). Unlike higher plants that had been genetically modified to produce taxa-4(5),11(1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(49 citation statements)
references
References 40 publications
1
46
1
1
Order By: Relevance
“…Some photosynthetic hosts such as cyanobacteria and eukaryotic moss tissue culture have already been demonstrated to be amenable to heterologous terpenoid expression (Anterola et al, 2009;Davies et al, 2014;Halfmann et al, 2014;Zhan et al, 2014). Eukaryotic microalgae as photosynthetic production platforms, however, are notoriously difficult to genetically engineer and there are limited reports on synthetic metabolic modifications of these organisms (Cordero et al, 2011;Kaye et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Some photosynthetic hosts such as cyanobacteria and eukaryotic moss tissue culture have already been demonstrated to be amenable to heterologous terpenoid expression (Anterola et al, 2009;Davies et al, 2014;Halfmann et al, 2014;Zhan et al, 2014). Eukaryotic microalgae as photosynthetic production platforms, however, are notoriously difficult to genetically engineer and there are limited reports on synthetic metabolic modifications of these organisms (Cordero et al, 2011;Kaye et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The presence and expression of the TS gene in the transgenic cultured ginseng root and the de novo formation of a compound with the same fragmentation pattern as taxadiene confirmed the successful transformation of cultured ginseng roots to produce taxadiene. The taxadiene yield from the transformed ginseng roots with the TS gene was 9.10 μg/g dry weight, which was higher than the 5 μg/g dry weight produced in moss (30), but lower than the 20 μg/g dry weight produced in transgenic tomato fruits (29).…”
Section: Discussionmentioning
confidence: 70%
“…Several studies have indicated methods to taxadiene in tomato and Arabidopsis using metabolic engineering due to the high price (29)(30)(31). The presence and expression of the TS gene in the transgenic cultured ginseng root and the de novo formation of a compound with the same fragmentation pattern as taxadiene confirmed the successful transformation of cultured ginseng roots to produce taxadiene.…”
Section: Discussionmentioning
confidence: 95%
“…35) P. patens was transfected with the biosynthetic gene for taxol and was confirmed to produce the biosynthetic intermediate. 36) Thus, these taxol-accumulating species including T. cuspidata, would be characterized as having the D26E mutation in common.…”
Section: Discussionmentioning
confidence: 99%